Exploration of Malay Art in Information Center Room Design at Tengku Anis Library - Ragil Tri Atmi; Siti Safingah (Literatify: Trends in Library Developments, 2023)
The design of the information center space has a role in creating the user experience. The interior design of the information center at Tengku Anis Library, Universiti Teknologi MARA (UiTM) Kelantan has a touch of local culture, namely Malay art in the form of wood carvings and batik art. The touch of local culture is an interesting and unique thing related to how local cultural elements affect the design of the information center space and its impact on users. This research uses the literature study method to describe the impact of the presence of Malay art on the design of the information center space. The purpose of the research is to analyze the inclusion of Malay art elements in the design of the information space at Tengku Anis Library. In addition to knowing how Malay art elements can be used as a tool for education and cultural understanding. Based on the results of the research, it was found that the touch of Malay art in the interior design of the room created a different atmosphere in the library. In addition, Malay artworks act as a means of cultural literacy for their users and become a means of preserving local culture. This research contributes to the context of design development in information centers, especially libraries, and will be able to provide insight into the importance of art integration in the design of information center spaces.